The creation of American common law, 1850-1880 : technology, politics, and the construction of citizenship - Schweber, Howard H. (Cambridge University Press, 2004)
This book is a comparative study of the American legal development in the mid-nineteenth century. Focusing on Illinois and Virginia, supported by observations from six additional states, the book traces the crucial formative moment in the development of an American system of common law in northern and southern courts. The process of legal development, and the form the basic analytical categories of American law came to have, are explained as the products of different responses to the challenge of new industrial technologies, particularly railroads. The nature of those responses was dictated by the ideologies that accompanied the social, political, and economic orders of the two regions. American common law, ultimately, is found to express an emerging model of citizenship, appropriate to modern conditions. As a result, the process of legal development provides an illuminating perspective on the character of American political thought in a formative period of the nation.